2021
DOI: 10.1136/jitc-2021-002694
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of viral antigens sharing sequence and structural homology with tumor-associated antigens (TAAs).

Abstract: BackgroundThe host’s immune system develops in equilibrium with both cellular self-antigens and non-self-antigens derived from microorganisms which enter the body during lifetime. In addition, during the years, a tumor may arise presenting to the immune system an additional pool of non-self-antigens, namely tumor antigens (tumor-associated antigens, TAAs; tumor-specific antigens, TSAs).MethodsIn the present study, we looked for homology between published TAAs and non-self-viral-derived epitopes. Bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…We have recently shown that TAAs may share high homology to viral antigens, suggesting an established antiviral memory T-cell immunity able to cross-react with tumor antigens [ 28 ]. Therefore, the predicted 28 SBs were further screened for homology to sequences derived from human viruses in BLAST, and several viral peptides were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that TAAs may share high homology to viral antigens, suggesting an established antiviral memory T-cell immunity able to cross-react with tumor antigens [ 28 ]. Therefore, the predicted 28 SBs were further screened for homology to sequences derived from human viruses in BLAST, and several viral peptides were found.…”
Section: Resultsmentioning
confidence: 99%
“…Homology analysis was performed to identify homology with viral epitopes, given that we have recently shown that such homology could represent a selective advantage in controlling tumor establishment and progression. Indeed, memory T cells induced by a previous viral infection could be promptly recalled to expand by tumor antigens, showing high homology with the viral antigens [ 28 , 29 ]. Out of the 28 SBs, 5 showed homology with viral epitope sequences including influenza virus, hepatitis C virus (HCV), hepatitis B virus (HBV), adenovirus, human cytomegalovirus (HCMV), and human calicivirus.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections elicit memory T-cells that may represent preventive anti-cancer vaccines. Homology between published tumor-associated antigens and non-self-viral-derived epitopes has been observed, with structural similarities between paired tumor-associated antigens and viral peptides as well as comparable patterns of contact with HLA and TCR α and β chains [ 96 ]. As such, viral antigens and tumor-associated antigens may elicit cross-reacting CD8 + T cell responses which could affect cancer progression.…”
Section: Drivers Of Immune Responsesmentioning
confidence: 99%
“…As such, viral antigens and tumor-associated antigens may elicit cross-reacting CD8 + T cell responses which could affect cancer progression. Previous exposure to specific viral epitopes may result in the establishment of a bispecific antiviral/anticancer T cell memory which may represent a relevant selective advantage for patients with cancer and provide a totally new set of antigens for developing a novel anticancer vaccine strategy [ 96 ].…”
Section: Drivers Of Immune Responsesmentioning
confidence: 99%
“…The improved prognosis in cancer patients bearing tumors expressing TuAs sharing sequence homology with viral antigens has been anecdotally reported in melanoma and pancreatic cancer [ 7 , 8 ]. Moreover, our group has shown very recently that several TAAs share sequence and structural homology with viral antigens [ 9 ] and that liver cancer cells presenting a mutated TSA mimicking the Vaccinia Virus (VV) antigen can be identified in a long-term survival patient with hepatocellular carcinoma (HCC) [ 10 ]. Finally, a decreased tumor growth and extended survival has been shown in a melanoma animal model presenting a TuA sharing sequence homology to a commensal’s antigen [ 11 ].…”
Section: Introductionmentioning
confidence: 99%